Functionalised biomimetic hydroxyapatite NPs as potential agent against pathogenic multidrug-resistant bacteria. (14th November 2019) - Bera, Debbethi; Pal, Kunal; Bardhan, Souravi; Roy, Shubham; Parvin, Rubia; Karmakar, Parimal; Nandy, Papiya; Das, Sukhen
Abstract: The persistent dissemination of resistant bacterial strains is a grave contemporary global impediment in hospital-acquired infections which needs to be mitigated with immediate effect. In particular, infections from pathogenic multidrug-resistant (MDR) Gram-positive bacteria (like Enterococcus faecalis ) which are resistant to conventional antibiotic therapy are attracting immediate global attention. Here we report the synthesis of nanoscale hydroxyapatites (HAPs), which are the well known biomimetic ceramic material having needle shaped morphologies. We have encapsulated vancomycin (VAN) within these nanoparticles and have conjugated the targeting ligand (folic acid) by a facile synthesis process in order to enhance the therapeutic efficacy against MDR E. faecalis . These functionalised HAPs are thoroughly characterised by employing field emission scanning electron microscopy (FESEM), powder x-ray diffraction (PXRD), ultraviolet–visible spectroscopy (UV-Vis) and dynamic light-scattering (DLS) techniques. Our results suggest that these functionalised HAPs could successfully transport vancomycin across the cell wall of MDR E. faecalis through endocytosis. The determination of selective antibacterial activity has been envisaged with the help of extensive in-vitro assays like the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and the generation of reactive oxygen species (ROS). This study vividly establishes that this folic acid conjugated HAPs are promising antibacterial agents against MDR E. faecalis and related pathogenic resistant bacterial strains.